Effect of methylphenidate on oculomotor function in individuals with multiple sclerosis: a pilot randomized placebo-controlled trial - Rich, Timothy J.; Alexander, Aubree; Dobryakova, Ekaterina; Chiaravalloti, Nancy D.; DeLuca, John; Costa, Silvana L (Frontiers in Neurology, 2024)
Introduction Individuals with multiple sclerosis (MS) frequently experience visual and oculomotor symptoms that may impact and confound neuropsychological assessments of information processing speed (IPS). In this study, we examined the effect of the psychostimulant methylphenidate on oculomotor function and the association between change in oculomotor speed and change in information processing speed. Methods We used a repeated measures crossover design in which a sample of 11 participants with MS were randomly assigned to one of two treatment arms: one that received methylphenidate for 4 weeks and another that received a placebo for 4 weeks. After a 7-day washout period, the treatments were crossed over. The King Devick test, the Symbol Digit Modalities Test, and the Paced Auditory Serial Addition Test were administered at baseline and after each of the two study arms. Results We found a significant improvement in oculomotor speed in the methylphenidate condition as compared to placebo. This improvement was significantly correlated with improvement on a visuomotor assessment of IPS (Symbol Digit Modalities Test), but no such association was found for an auditory-verbal assessment of IPS (Paced Auditory Serial Addition Test). Discussion These findings suggest that individuals with MS experience improved oculomotor speed while taking methylphenidate, which may, in turn, improve performance on assessments of IPS with visuomotor demands.